2021
DOI: 10.1177/23259671211000459
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Kinematic Analysis of Lateral Meniscal Allograft Transplantation With Soft Tissue Fixation

Abstract: Background: Lateral meniscal deficiency increases the pivot shift in the knee, and although meniscal allograft transplantation (MAT) is a well-established procedure with satisfactory clinical results, biomechanical studies have failed to show whether this procedure is able to restore knee kinematics. Purpose: To assess, in vivo, the kinematic effect of lateral MAT in anterior cruciate ligament–intact knees, with a particular focus on the pivot-shift maneuver. Study Design: Controlled laboratory study. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“… 13 , 27 , 37 MAT was also shown to reduce tibial translation and anterior cruciate ligament (ACL) stress because of its function as a secondary stabilizer. 27 , 29 , 60 However, it is still not clear whether this procedure prevents or slows down cartilage degeneration, consequently delaying knee arthroplasty surgery. 1 , 24 , 45 , 54 , 55 Moreover, although several studies have demonstrated the good results of MAT in young patients with otherwise healthy knees, 6 , 26 , 35 , 57 the application of MAT as a salvage procedure in OA joints remains controversial.…”
mentioning
confidence: 99%
“… 13 , 27 , 37 MAT was also shown to reduce tibial translation and anterior cruciate ligament (ACL) stress because of its function as a secondary stabilizer. 27 , 29 , 60 However, it is still not clear whether this procedure prevents or slows down cartilage degeneration, consequently delaying knee arthroplasty surgery. 1 , 24 , 45 , 54 , 55 Moreover, although several studies have demonstrated the good results of MAT in young patients with otherwise healthy knees, 6 , 26 , 35 , 57 the application of MAT as a salvage procedure in OA joints remains controversial.…”
mentioning
confidence: 99%